Clinical Presentation and Outcome of Fibrous Dysplasia in Patients attending Sahiwal Teaching Hospital, Punjab. - Raees Abbas Lail; Amir Majeed (University of Lahore, 2022)
Objective: To study the clinical presentation, management and outcome of Fibrous Dysplasia in patients admitted in Neurosurgery Department of Sahiwal Teaching Hospital, Punjab. Methods: This retrospective descriptive observational study was conducted in the months of January-June, 2021 on 20 patients with histologically confirmed Fibrous Dysplasia whose records were obtained from the hospital laboratory data base admitted between January 2017 to January 2021. The age of the patients, gender, socioeconomic status and length of stay of patients was also recorded. Clinical presentation and exact location on x-rays of the lesion, surgical intervention and clinical outcome were tabulated. Results: This condition was common in the age range of 25-50 years, affected both genders equally, was more prevalent in low socioeconomic group and prolonged the length of stay of patients to 3-4 weeks. It was observed from the radiographs of the patients that ethmoid bone was most commonly eroded (75%) followed by sphenoid (60%) and frontal bone (25%), 2 cases involved the maxillary bone (10%) and in one case it infiltrated the zygomatic bone (5%). The most common presenting features included visual deterioration and proptosis. Surgical intervention ranged from biopsy and conservative treatment to craniotomy and resection. There was no mortality recorded. Conclusion: Patients with fibrous dysplasia most commonly present with visual deterioration. Although it is a benign disease, but surgical intervention is required for cosmetic purposes. Keywords: Fibrous dysplasia, computed tomography (CT), magnetic resonance imaging (MRI).